Penyelesaian Kasus Penyerobotan Tanah Melalui Aspek Hukum Acara Pidana - Liza Deshaini; Fitra Aryadi; M. Zafri Alem; Eva Susanti; Badai Baras Siregar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Various regions in Indonesia have a history of land abduction. Taking, occupying, or taking another's land illegally is known as land abduction. The following factors cause land abduction: human greed or greed, economic factors, employment factors, and educational factors. The process of settling a case of land abduction in the Criminal Procedure Law is as follows: report or complaint, filing of a case to the prosecutor general, the plaintiff, the indictment, the trial, the reading of the charges, the exemption, the examination of the means of proof, the complainant, the defence of the replica, the duplication, the judgment of the court, the ordinary and extraordinary legal effort.